Optimal control of a rumor propagation model with different propagation degrees in social network / Tang Yingfeng - Tang, Yingfeng (2020)
Rumor is a social interaction of information, and its development is of great significance to human beings. In this paper, by studying the D K model and a rumor model spreading with rumor latent period, deduces the rumor model with differe nt propagation degrees of the spreaders. The two equilibrium points in the system are found through derivation. In real life, enterprises often ignore the reasonable planning of the cost of rumor control. By means of public education and media technology u sing by the authorities to debunk rumors, an optimal control problem i s established. The Pontryagin’s maximum principle is combined with the Hamilton ian function. Bang bang control enables the linear control set U to get the optimal solution in the nonlinear cost problem. MATLAB was used for simulation, and the visualization results of the rumor model were obtained. Finally, the research on rumor is summarized to optimize the cost of rumor control.